THE DEVELOPING LISTENING SKILL THROUGH YOUTUBE CHANNEL MEDIA FOR STUDENTS AT PRIMARY SCHOOL - Endang Iryani; Dwi Puspita; Akhmad Subki Ramdani (Universitas Duta Bangsa Surakarta, 2024)
The study aims to know the effect of Kids YouTube channels on building English listening skills in children. It is known that the selected channel can improve children’s listening skills, particularly by enriching their English vocabulary. This research used experiment method, sample was students third grade Elementary School at SDN 16 Kramat Jati. The result of research is YouTube channel Kids to improve students listening skills, the writer concludes that English song media on YouTube channel Kids improved the students listening skills. It can be seen from the students listening scores between before-used English song media on the YouTube channel and after-used English song media in the learning activity. In the score pre-test or before using English song media on YouTube channel kids in learning activity, the result showed that the mean of the students was 57.91, and after using English song media on YouTube channel kids in learning activity, the result from the mean of the students in the score post-test was 61.89. It means the score of the post-test was higher than the score of the pre-test. So it can be concluded that there was a different score to better when using English song media on YouTube channels for kids in the class.